2018
DOI: 10.1111/pim.12603
|View full text |Cite
|
Sign up to set email alerts
|

High macrophage activities are associated with advanced periductal fibrosis in chronic Opisthorchis viverrini infection

Abstract: Liver fluke infection caused by Opisthorchis viverrini induces several hepatobiliary conditions including advanced periductal fibrosis (APF) and cholangiocarcinoma (CCA), but >25% of the infected population develops APF and 1% develop CCA. The innate immune response is the first line of defense, and macrophages are critical regulators of fibrosis. We hypothesized that macrophages from infected individuals have different capacities to either promote or suppress periductal fibrosis. We compared phagocytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…A significantly higher number of macrophages in the lamina propria have been reported during the early stages of O. viverrini infection in hamsters [ 12 ]. In this stage, macrophages primarily contribute to producing free radicals, which act as cytotoxic effectors, promote tissue injury, and damage DNA [ 38 40 ]. Our data further explains the relationship between free radical production and DNA damage in susceptible and non-susceptible animals.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher number of macrophages in the lamina propria have been reported during the early stages of O. viverrini infection in hamsters [ 12 ]. In this stage, macrophages primarily contribute to producing free radicals, which act as cytotoxic effectors, promote tissue injury, and damage DNA [ 38 40 ]. Our data further explains the relationship between free radical production and DNA damage in susceptible and non-susceptible animals.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages were detected among the granulomatous tissue, consistent with previous studies ( Sripa and Kaewkes, 2000a ; Lvova et al ., 2012 ). During O. viverrini infection, macrophages with high phagocytic and proteolytic activities, along with elevated ROS production, can promote tissue damage leading to PDF ( Salao et al ., 2019 ). IL-4 and IL-13, based on Th2 response, stimulate macrophages to become alternatively activated macrophages (AAMs) or M2, which secrete mediators with a slow-killing effect on helminths ( Yasuda and Nakanishi, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…At least, the M1/M2 ratio was higher in the older group and its correlation with collagen deposition suggests that inflammation is involved in the aging process and fibrosis development ( Figure 3 ). M1 can switch to M2 [ 38 ], and high levels of M2 were expressed in NAC treatment group suggesting the anti-inflammatory effect of NAC on anti-fibrosis during the process of physiological aging and the possible mechanism underlying M2 polarization ( Figures 3 and 4 ). However, some researchers indicated that continuous activation of M2 macrophages may impair tissue regeneration and function by promoting fibrosis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%